2019
DOI: 10.1177/1179543319856022
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Influence of Larval Density on Disease Transmission Indices inCulex quinquefasciatus, the Major African Vector of Filariasis

Abstract: Larval crowding is one of the abiotic factors affecting biological fitness in mosquitoes. This study aims at elucidating, quantitatively, the influence of more larval crowding on aspects of fitness in Culex quinquefasciatus mosquito. To this end, day-old larvae of the species were reared in 4 density regimens equivalent to 1 larva in 1.25, 2.5, 5, and 10 mL of distilled water. Developmental indices, adult fitness indices, and accumulation and utilisation of teneral reserves for metamorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…funestus under laboratory conditions in different geographical areas. The longevity and survival of the resultant adults were not investigated in this study as previous studies have revealed negative effects of high larval density on post‐emergence adult longevity and survival (Ombok et al, 2002; Reiskind & Lounibos, 2009; Ukubuiwe et al, 2019). However, this needs to be confirmed in this species.…”
Section: Discussionmentioning
confidence: 99%
“…funestus under laboratory conditions in different geographical areas. The longevity and survival of the resultant adults were not investigated in this study as previous studies have revealed negative effects of high larval density on post‐emergence adult longevity and survival (Ombok et al, 2002; Reiskind & Lounibos, 2009; Ukubuiwe et al, 2019). However, this needs to be confirmed in this species.…”
Section: Discussionmentioning
confidence: 99%
“…In Cx. quinquefasciatus, fourth larval instars were most affected by increasing larval density, and resulted in reduced rate of larval growth and immature life survivorship of the species [126]. These authors opined that high larval densities induce stress and reduced feed intake due to competition, with reduction in metabolic reserves.…”
Section: Larval Density/overcrowdingmentioning
confidence: 99%
“…aegypti [125]. Overcrowding conditions increase larval development times [121], but reduce the size of the mature larva, pupa and resulting adult [126], with its attendant effects on the fecundity of females [127].…”
Section: Larval Density/overcrowdingmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, larvae raised with rapidly decaying plant detritus have similarly better larval performance than larvae raised with slow-decaying plant detritus [14,15,16,17]. In turn, differences in larval performance as a result of detritus type have been related to adult body size [13,14,18] and survival [17,19], while variation in available larval food resources more generally have also been related to fecundity [20,21,22], biting rate [23], and susceptibility to viral infection [24,25,26], all of which are expected to affect disease transmission at the individual and population scales [27,28,29,30,31,32]. Although resource competition is often the dominant ecological process regulating mosquito populations in ephemeral habitats, populations may also be regulated by abiotic factors, including litter-based toxins.…”
Section: Introductionmentioning
confidence: 99%